Present and future scope of recombinant parathyroid hormone therapy in orthopaedics - Sain, Arnab (J Clin Orthop Trauma, 2021)
Parathyroid Hormone (PTH) has a significant role in calcium metabolism. Its intermittent administration has an anabolic effect on bone mineralization. Teriparatide (PTH 1-34), a recombinant form of parathyroid hormone, is useful in the treatment of osteoporosis, fracture healing, non-union, stress fracture, augmentation of implant fixation with bone, and chondroprotection in osteoarthritis. The present review article will elaborate on the potential approved uses of recombinant PTH in orthopedics and its evolving role in the management of fracture osteosynthesis and other common challenging bone pathologies.